Analysis Of Competency, Workload And Job Fatigue On Employee Performance In PT. Indokom Citra Persada - Putri Syahranti Tanjung; Hasrul Azwar Hasibuan; Muhammad Toyib Daulay (Jurnal Fokus Manajemen, 2026)
This study aims to analyze Competence, workload, and work fatigue on employee performance at PT Indokom Citra Persada. This study uses a quantitative method involving 78 employees as respondents. Data collection was carried out using questionnaires. The data obtained were analyzed using statistical formulas, namely by using the normality test, multicollinearity test, heteroscedasticity test, and multiple linear regression analysis with the SPSS Version 23.0 program. The results of this study indicate that the t-value of 5.704 is greater than the t-table of 1.99 with a significance level of 0.000. Thus, H1 is accepted and H0 is rejected, which means that competence has a positive and partially significant influence on employee performance. The t-value of 2.976 is greater than the t-table of 1.99 with a significance level of 0.004. Thus, H2 is accepted and H0 is rejected, which means that workload has a positive and partially significant effect on performance. The t-value of -0.010 is smaller than the t-table of 1.99 with a significance level of 0.912. Thus, H3 is rejected and H0 is accepted, which means that fatigue has a negative and partially insignificant effect on performance. The F-value of 2.73. Because the F-value of 19.089 is greater than the F-table of 2.73, it can be concluded that the variables of competence, workload, and fatigue have a significant effect simultaneously on performance.